STUDI TENTANG PERSEPSI MASYARAKAT TERHADAP PERANAN KOMITE SEKOLAH DI DMPN 1 TANDUN KABUPATEN ROKAN HULU - Pamungkas, Sawitri; Eddison, Ahmad; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The role of the school committee is the advisor (advisory) in determining and implementing educational policies in the education unit, supporting both in the form of financial, thought, and personnel in the administration of education in the education unit, controlling in the framework of transparency and accountability in the implementation and education output in the education unit, and mediator between the government (executive) and the community in the education unit. This study aims as follows: to find out Community Perceptions of the Role of School Committees at SMPN 1 Tandun, Rokan Hulu Regency. The subjects of this study were all 900 parents/guardians of SMPN 1 Tandun, Rokan Hulu Regency.The sample in this study was taken based on the snowball sampling technique with 10% of subjects from 900 parents/guardians. Data collected through observation, questionnaires, interviews, and documentation. In analyzing data using quantitative descriptive techniques.The results showed that school committee members were very instrumental in carrying out the role of school committees in SMPN 1 Tandun Rokan Hulu Regency, this was evidenced by the results of the calculation of respondents who answered